THE IMPACT OF COMBINATION OF BREASTFEEDING AND EFFLEURAGE MASSAGE IN REDUCING PAIN RESPONSE IN INFANTS INDUCED BY BLOOD SAMPLING IN C-REACTIVE PROTEIN TEST: AN OBSERVATIONAL CROSS-SECTIONAL STUDY - Alfi Maziyah; Diyah Fatmasari; Desak Made Wenten Parwati; Rr. Sri Endang Pujiastuti (Belitung Raya Foundation, Indonesia, 2018)
Background: C-reactive protein test is one of clinical assessments to minimize risks of infection in infants. However, its procedure may cause pain. Pain in the infants may result in negative metabolic behavior, physiology and metabolic response. Objective: This study was to describe the infant's pain response by administering a combination of breastfeeding and an effleurage massage on the blood sampling procedure of C-reactive protein examination. Methods: This was a descriptive observational cross-sectional study. There were 30 infants selected using consecutive sampling technique, which 15 samples assigned in an intervention group (combination of breastfeeding and effleurage massage) and a control group. Premature Infant Pain Profile (PIPP) instrument was used to measure pain. Univariate analysis was performed with the aim to describe data in mean and median. Results: The average of pain response at one-minute observation in the combination of breastfeeding and effleurage massage group was 7.47 ± 1.356, and the average of pain response in the control group was 10.80 ± 1.897. The average pain at five-minutes observation in the intervention group was 3.53 ± 1.922 and control group was 6.00 ± 1.852. Conclusions: Pain responses in the combination of breastfeeding and effleurage massage group were lower than the pain response in the control group.